Humanisten uit de Lage Landen in Hongarije in de 16de eeuw - Bitskey, István (Acta Neerlandica, 2015)
The early history of the connections between Netherlands and Hungary is connected with the catholic restoration in the Kingdom Hungary in the middle of 16-th Century. In this time came the famous humanist Nicasius Ellebodius to Hungary. He studied in Louvain and Rome in the Collegium Germanicum, and at the invitation of Miklós Oláh, Archbishop of Esztergom he arrived to Nagyszombat (today: Trnava in Slovakia), to the centre of Hungarian Catholicism. He taught there Greek and Latin language and literature in the newly-established college of the Society of Jesus. Another Netherlander, Guilelmus Sulenius de Flandria, studied likewise in Rom, and then came to Hungary. Archbishop Oláh invited himto teach at Pozsony (today:Bratislava in Slovakia), and he was granted a prebend in recognition of his work. Besides they other Netherlandish teachers and professors (e.g. Arnoldus Gerardus Laurentianus Flandrus, Jacobus Somalius etc.) took part in the reorganisation of the Catholic school-training and they played an very significant and important role in the intellectual life in early modern Hungary